A computational investigation on the influence of the l/d ratio and strain rate on the deformation behavior of rolled and homogeneous armor steel in the split Hopkinson pressure bar test process. (February 2022) - Saxena, Ambuj; Dwivedi, Shashi Prakash; Srivastava, Ashish K; Sharma, Shubham; Kotkunde, Nitin
The present investigation deals with the finite-element analysis of the high strain rate deformation behavior of the quenched and tempered armor-grade rolled and homogeneous armor steel. The rolled and homogeneous armor steel is extensively used in civil and military structures such as battle tanks, armament combat vehicles, combat helicopter, etc. The dynamic deformation behavior of rolled and homogeneous armor steel, that is, resistance against ballistic circumstances relates to its mechanical behavior under high strain rate conditions. In the present research work, a finite-element analysis investigation (using Abaqus finite-element analysis code) has been carried out to evaluate the influence of specimen l/d ratios and high loading strain rates on the deformation behavior and stress–strain responses of the rolled and homogeneous armor steel. Further, an attempt has also been made to check the high strain rate and specimen l/d ratio influence on the strain amplitudes of incident, reflected, and transmitted pulses. The numerical investigation has been carried out with the rolled and homogeneous armor steel specimen with l/d ratios of 1, 0.8, and 0.6. In addition, three high impact strain rates of 2130, 2907, and 3105 s −1 are considered to evaluate the stress–strain responses. The results revealed that the l/d ratio and strain rate have a significant influence on the specimen stress–strain response and the strain amplitudes of incident, reflected, and transmitted pulses. The peak stress value is increased with the increase in the l/d ratio and strain rate. The developed finite-element analysis model has predicted the stress–strain responses with <3% percentage error. The obtained finite-element analysis results have been validated with the experimental investigation with an l/d ratio of 0.6 and a strain rate of 3105 s −1 for rolled and homogeneous armor steel.